Fixed income markets : management, trading and hedging - Choudhry, Moorad (John Wiley & Sons, 2014)
"Takes a unique look into the leading practices in bond markets as well as post-credit-crunch impacts on pricing that are rarely captured in textbooks. The new edition provides expanded coverage on a wide range of topics within hedging, derivatives, bonds, rebalancing, and global debt capital markets."--Provided by publisher